2018
DOI: 10.1016/j.redox.2017.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Akt activity by CYP2E1 mediated oxidative stress is involved in chronic ethanol-induced fatty liver

Abstract: Protein kinase B (PKB/Akt) plays important roles in the regulation of lipid homeostasis, and impairment of Akt activity has been demonstrated to be involved in the development of non-alcoholic fatty liver disease (NAFLD). Previous studies suggest that cytochrome P4502E1 (CYP2E1) plays causal roles in the pathogenesis of alcoholic fatty liver (AFL). We hypothesized that Akt activity might be impaired due to CYP2E1-induced oxidative stress in chronic ethanol-induced hepatic steatosis. In this study, we found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 62 publications
(109 reference statements)
2
54
0
1
Order By: Relevance
“…E). Akt is used to indicate hepatocyte viability, as it is suppressed in oxidative stress‐induced liver injury; thus, Akt activator protects hepatocytes from apoptosis and alleviates endotoxin‐induced liver injury . As expected, GW3965 treatment prevented decrease of p‐Akt (Fig.…”
Section: Resultssupporting
confidence: 65%
“…E). Akt is used to indicate hepatocyte viability, as it is suppressed in oxidative stress‐induced liver injury; thus, Akt activator protects hepatocytes from apoptosis and alleviates endotoxin‐induced liver injury . As expected, GW3965 treatment prevented decrease of p‐Akt (Fig.…”
Section: Resultssupporting
confidence: 65%
“…CYP2E1 is one of the main enzymes in MEOS and plays a vital role in ethanol metabolism (Doody et al, 2017;Yuan et al, 2018). After excessive drinking or drinking a high concentration of alcohol, the activity of CYP2E1 is promoted and resulting in excessive reactive oxygen species (ROS) (Chen., 2014;Zeng et al, 2018). Then large amounts of reducing substances in the tissue including SOD and GSH-Px are consumed; alcohol-induced GSH-Px and SOD consumption are thought to aggravate oxidative damage in ALD mice model (Cederbaum, 2013;Zeng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…After excessive drinking or drinking a high concentration of alcohol, the activity of CYP2E1 is promoted and resulting in excessive reactive oxygen species (ROS) (Chen., 2014;Zeng et al, 2018). Then large amounts of reducing substances in the tissue including SOD and GSH-Px are consumed; alcohol-induced GSH-Px and SOD consumption are thought to aggravate oxidative damage in ALD mice model (Cederbaum, 2013;Zeng et al, 2018). The remaining lots of ROS cannot be inactivated, which also promotes the production of toxic lipid intermediates FIGURE 10 | Effects of magnolol on NLRP3 inflammasome, caspase-1 and caspase-3 signaling pathway in ALD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has suggested that oxidative stress plays a central role in the development of alcoholic liver injury (Dey & Cederbaum, ). During alcohol metabolism, alcohol can induce a hypermetabolic state in the liver and be selectively metabolized by the activated cytochrome P4502 E1 whose overexpression, from which much H 2 O 2 is generated producing cell damage (Zeng et al., ). The generation and accumulation of reactive oxygen species (ROS), together with the inhibition of antioxidant system by alcohol, result in oxidative stress and subsequently promote cell apoptosis or death by overwhelming the intrinsic antioxidants, depleting glutathione, and enhancing oxidative damage (Foadoddini et al., ; Ji et al., ).…”
Section: Introductionmentioning
confidence: 99%